(untitled) (Sound Stage Screen, 2021)
This article offers a case study of how revivals of two early nineteenth-century French melodramas have enabled interdisciplinary dialogue on moving from the textual study of melodrama to historically informed performance. Bringing together the text, the score and acting allows us to gain a much better understanding of the ways in which these elements interacted., Piecing together clues about the play as a performance in the process of preparing for 21st-century historically informed staging is a task similar to that of an archaeologist reassembling an old pot from a handful of pieces. This metaphor of archaeology comes from Mike Pearson and Michael Shanks’ seminal text Theatre/Archaeology and James Mathieu, Introduction to Experimental Archeology : replicating past objects, behaviors and processes. Shanks and Pearson in particular highlight the centrality of interpretation in both archaeology and performance and see both spheres as connected by a common aim to retrieve and reconstruct ephemeral events and understand the textures of the social and cultural experience of the object in the past. Exploring the idea of archaeology as a metaphor for our work helped us reach a clearer understanding of text, music and genre in melodrama.